PENGARUH KECENDRUNGAN MANAJER DALAM PENGAMBILAN KEPUTUSAN TERHADAP PAYOFF MAGNITUDE - Sri Madona Shaleh; Khairul Marlin; Lasmi Yupita (Imara: JURNAL RISET EKONOMI ISLAM, 2020)
The research purposes were to describe empirically the evidence of manager’s tendency in making decisions on payoff magnitude, and factors influencing it. This research was conducted through experimental design. Population was 152 students of STIE “KBP” Padang registered in 2014/2015 academic year. 60 students randomly were taken as sample of the research; 30 students of accounting department as treatment group, and 30 students of management department as control group. From the research results, it can be seen a significance difference between the manager's tendency in decision making towards Payoff Magnitude, as well as the factors that influence it. The results also showed experiment group tended to be risk taker rather than control group.